Study on deformation characteristics and dynamic cause of the Luding MS6.8 earthquake - Yuan, Zhengyi; Zhao, Jing; Huang, Yuan; Yu, Huaizhong; Niu, Anfu; Ma, Haiping; Ma, Lingli (Frontiers in Earth Science, 2023)
A MS6.8 earthquake struck Luding Country in Ganzi Prefecture, Sichuan Province on September 5, 2022. The earthquake occurred on the Moxi segment of Xianshuihe fault zone (XFZ), one of the most seismically active faults in the Chinese mainland. In this study, multiple periods of the Global Positioning System (GPS) velocity field and continuous observational data are collected to analysis the tectonic deformation and evolution characteristics before the Luding earthquake, from the perspectives of the kinematic behavior of seismogenic fault, the multi-scale strain features around the study region, and the variation of GPS baselines across the epicenter area. Then the following conclusions are obtained: (1) The accelerated compression of baselines SCGZ-SCXJ (Ganzi to Xiaojin in Sichuan province) and SCLH-SCXJ (Luhuo to Xiaojin in Sichuan province) in Bayan Har block indicate that under the influence of the coseismic rupture of Maduo MS7.4 earthquake, the boundary faults decoupled and accelerated the push southward and eastward, leading to the acceleration of strain accumulation and the increase of seismic risk in the divergence area bounded by the southeastern XFZ and the southwestern Longmenshan fault zone (LFZ). ( 2) Luding earthquake located in the weakened region around the edge of the large strike-slip fault zone with high shear strain rate, and the tensile zone of the strain perpendicular to the fault direction, denoting that the reduction of the normal strain in the locked background is strongly related to fault rupture and earthquake nucleation.